Lost in translation: the need for qualified medical interpreters - Sangah, Abdul Basit; Saleem Shaikh, Shazia; Khalid, Muhammad Zain (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Pakistan is home to various cultures and varied languages. We are writing this letter to share our insights and to emphasize the essential need for highly trained medical interpreters in Pakistan's healthcare system, particularly in different urban locations like Karachi. As a multilingual city with many immigrants and visitors from other provinces and countries, efficient communication is vital for outstanding service. However, we have noticed in the public and private Outpatient Departments (OPDs) that hospital-appointed interpreters frequently lack the information, training, and qualifications necessary for proper medical interpretation. Hale found in her study that untrained interpreters may not comprehend the reasons behind certain procedures, particular questions, or styles of delivery in varied situations, as well as the value of the layperson’s replies in enabling the healthcare workers to fulfill their tasks efficiently and correctly.1 We discovered especially in Infectious and Internal Medicine OPDs of teaching hospitals that inexperienced translators typically ignore or alter clinical information, failing to convey essential information. Furthermore, the patients feel uneasy revealing their confidential worries with a translator. Consequently, essential subtleties are missed, complicating diagnosis and therapy. With patients traveling from distant areas, like Afghanistan and Iran, failed communication on a single visit, becomes detrimental. Using qualified medical interpreters is associated with improved clinical outcomes, patient satisfaction and adherence. M. Shoaib et, al. suggested a potential solution to tackle this issue by recommending that medical professionals from all backgrounds sign up to volunteer as translators and that each tertiary care facility have a group of language facilitators who are readily available in the hospital so that patients may provide first-hand health information without any barriers,2 however it could be difficult to achieve this. Moreover, Bashir. S mentioned in her thesis that the ability of therapists to interact with patients and establish a therapeutic bond is significantly impacted by the presence of trained interpreters.3 Hence better training must be provided to interpreters to improve their clinical knowledge and expertise in treatment. To ensure that all patients in Karachi get excellent treatment, regardless of language barriers, we encourage healthcare institutions to hire properly certified translators. If finances pose a barrier, existing employees could undergo rigorous, standardized training on medical vocabulary, ethics and communication strategies. Such initiatives will facilitate empathetic communication, foster shared understanding, and ultimately lead to better health outcomes.